Relationship between Supervisor Social Support and Burnout in Nurses - F Mohammadi-Fakhar; F Rafii; R Heshmat; H Haghani (Iran University of Medical Sciences, 2012)
Background and Aim: Burnout is a common syndrome in people who spend their time on providing support to others. Nurses are particularly susceptible to burnout, because of the nature of their profession. Workplace social support is one of the ways to reduce burnout. So the aim of this study was to determine the relationship between supervisor social support and burnout in nurses.   Material & Methods: It was a descriptive correlational study. Two hundred nurses working in hospitals affiliated to Tehran University of Medical Sciences were recruited by proportionate stratified sampling. The instruments included Maslach Burnout Inventory (MBI) and the Support Appraisal for Work Stressors Inventory (SAWS). Data were analyzed by descriptive statistics and Pearson correlation coefficient using (SPSS)-PC (18).   Results: The majority of nurses experienced high levels of emotional exhaustion and lack of personal accomplishment (61% and 97% respectively), and moderate levels of depersonalization (59%). The mean supervisor social support scores were 2.03-2.1 in various dimensions. Significant relationship was found between all dimensions of supervisor social support and frequency of depersonalization. Moreover, there was significant relationship between emotional and informational dimensions of supervisor social support and frequency of personal accomplishment (P<0.05).   Conclusion: Administrators can reduce nurses' burnout with the appropriate workplace social support. Further studies are suggested to assess and compare other factors related to burnout.   Received: 21 Dec 2012   Accepted: 16 Mar 2013